Factors influencing financial leverage of consumer products sector in Malaysia / Nur Syarifa Akmal Ahmad Ghazali - Ahmad Ghazali, Nur Syarifa Akmal (2014)
This study aimed to investigate which factors that influence financial leverage in consumer products sector in Malaysia. In addition, this research also wants to find what theory of capital structure that consumer products sector consistent with. The sample consists of 90 companies that are listed in the Main Board of Bursa Malaysia from 2004 to 2013. The independent variables selected for this study are tangibility, profitability, size of firm, growth opportunities, liquidity and non-debt tax shield. Debt ratio is the dependent variable in this research. The results show that financial leverage of consumer products sector in Malaysia is influenced by tangibility and size of firm. Another variable such as profitability, growth opportunities, liquidity and non-debt tax shield are found to have no explanatory in this model. Tangibility, growth opportunities, liquidity and size of firm have positive relationship with debt ratio, meanwhile, profitability and non-debt tax shield are negatively related with debt ratio. In addition, the results indicate that consumer products sector in Malaysia is consistent with Trade-off theory and Pecking Order theory.